A case of bilateral vertebral artery dissecting aneurysms presenting with subarachnoid hemorrhage evaluated using computational fluid dynamics: Which is the rupture side? - Masanori Tsuji; Fujimaro Ishida; Ryuta Yasuda; Tomonori Ichikawa; Takenori Sato; Kazuhiro Furukawa; Yoichi Miura; Yasuyuki Umeda; Naoki Toma; Hidenori Suzuki (Brain Hemorrhages)
Background: Saccular aneurysms (SAs) have been long studied in hemodynamics using computational fluid dynamics (CFD), while dissecting aneurysms (DAs) remain unclear. To estimate which side of the aneurysm ruptured, we evaluated the hemodynamics of the bilateral vertebral artery DAs (VADAs).Case presentation: A 44-year-old male was diagnosed with subarachnoid hemorrhage by the rupture of either side of bilateral VADAs. The rupture side could not be determined on admission (Day 0). CFD was performed using a patient-specific geometry model obtained from 3-demensional (3D) rotational angiography (RA) on day 1. We predicted that the right DA had ruptured based on the hemodynamics, associated with flow stagnation and complexity in the ruptured SAs by a transient analysis with the patient-specific blood flow velocity waveforms. After careful observation, gadolinium-enhanced MRI on day 16 showed a contrast effect in the right wall and a change in the right shape was confirmed on the second 3D RA on day 17. According to both imaging evaluations and CFD, the right was presumed to be ruptured, and a flow-diverter stent was placed at the right VA. The right VADA did not re-rupture for 12 months.Conclusion: Our results indicated that hemodynamics of ruptured DAs would be similar to that of ruptured SAs.